Studio Management System - Mohd Noh, Faizul (2002)
The Studio Management System is a prototype of management and online system reference for the management, the client and also for the staff in a postproduction company. This system uses a web based application and also active server page for a local area network in a small-scale postproduction business. As for the database, Microsoft Access is being used. The Studio Management System consists of 3 main applications, which are The Studio Booking System, The Tape Tracking System, and lastly is The Staff Attendance System. Based on these systems, 3 main reports are created, that are Studio Report, Tape Report and Attendance Report. This report can only be view by the management and the Webmaster does the updating and database management. Based on these report, any accrued hours and tape material can easily be detected and extra charges can be billed to the client.